2021
DOI: 10.3389/fmed.2021.642615
|View full text |Cite
|
Sign up to set email alerts
|

C3AR1 mRNA as a Potential Therapeutic Target Associates With Clinical Outcomes and Tumor Microenvironment in Osteosarcoma

Abstract: Objective: Targeting cancer-specific messenger RNAs (mRNAs) may offer novel insights into therapeutic strategies in osteosarcoma. This study aimed to discover possible osteosarcoma-specific mRNA and probe its biological functions.Methods: Based on mRNA-seq data from the TARGET database, stromal and immune scores were estimated for each osteosarcoma sample via the ESTIMATE algorithm. Stromal and immune mRNAs were obtained via integration of differentially expressed mRNAs between high and low stromal / immune sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…The overexpression of C3AR1 mRNA was confirmed to inhibit the proliferation, migration, and invasion of OS cells and induce apoptosis. It may be a promising therapeutic target for OS, and it may be related to prognosis and the tumor microenvironment ( 29 ). M6A regulators (i.e., FTO and IGF2BP2) may play an important role in the metastasis of OS, which is of great value to the prognosis and treatment strategy for OS patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of C3AR1 mRNA was confirmed to inhibit the proliferation, migration, and invasion of OS cells and induce apoptosis. It may be a promising therapeutic target for OS, and it may be related to prognosis and the tumor microenvironment ( 29 ). M6A regulators (i.e., FTO and IGF2BP2) may play an important role in the metastasis of OS, which is of great value to the prognosis and treatment strategy for OS patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…C3AR1 mRNA expression was positively correlated to the infiltration levels of various immune cells such as macrophages [ 26 ]. EBI2 expression directs the date of Tfh cells by promoting their interaction with IL-2-quenching dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zou et al. found that C3AR1 promoted the apoptosis of osteosarcoma cells and was closely related to the infiltration of several immune cells such as macrophages M1, macrophages M2, CD8 + T cells and so on [32] . In our research, the GSEA results revealed that the apoptosis-associated risk related to several immune pathways such as B cell receptor signaling pathway and intestinal immune network for IgA production.…”
Section: Discussionmentioning
confidence: 99%